Complex and Thermodynamic Properties of Polar Liquids Using Time Domain Reflectometry in Microwave Frequency (European Journal of Engineering Science and Technology, 2019)
The complex permittivity spectra and thermodynamic properties of 1,2-dichloroethane (DE) and n,n-dimethylformamide (DMF) polar liquids have been obtained at 15°C temperature in the frequency range of 10 MHz to 30 GHz by using time domain reflectometry technique for 11 different concentrations of the system. Time-dependent data is processed to obtained complex reflection coefficient spectra ?*(?). Complex permittivity spectra are obtained from bilinear calibration method and these spectra give information regarding dielectric dispersion (??) and dielectric absorption ?(??), which indicates the purity of the liquid mixture. The modified Bruggeman model is also a parameter that may be used as an indicator of liquid 1 and 2 interactions. In the binary mixture of polar liquids, there is a change in the energy of the system. This change in energy can be interpreted with thermodynamic parameters such as free energy of activation (?G), molar enthalpy of activation (?H) and molar entropy of activation (?S).